2008
DOI: 10.1111/j.1365-2699.2007.01866.x
|View full text |Cite
|
Sign up to set email alerts
|

Patterns in vegetation and sedimentation during the Weichselian Late‐glacial in north‐eastern Germany

Abstract: Aim To identify and interpret spatial patterns of vegetation and sedimentation during the Weichselian Late-glacial.Location North-eastern Germany and the adjacent fringe of north-western Poland.Methods An inspection and comparison of palynological data from c. 150 sites.Results Open Vegetation phase I (Oldest Dryas = earlier part of the Meiendorf, 12,900-12,450 14 C bp) and the Hippophaë phase (Bølling = later part of the Meiendorf; 12,450-12,000 bp) were rather homogeneous palynologically in the study area. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
65
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(72 citation statements)
references
References 34 publications
4
65
2
Order By: Relevance
“…The assemblage comprises a low dwarfshrub canopy of Betula nana, Salix type B, and Andromeda polifolia, similar to the rim vegetation but containing a higher proportion of plants that have a greater water tolerance or occur commonly in raised bogs, such as Carex. In contrast to our study, Minke et al (2009) andDonner (2007) carried out comparable vegetation analyses in the northern Indigirka Lowland and identified Comarum palustre, Drepanocladus revolvens and Sphagnum squarrosum as common elements of vegetation in the rim-to-pond transition zone (in addition to Carex and Andromeda polifolia; de Klerk, 2008).…”
Section: Small-scale Spatial Structure Of Polygonscontrasting
confidence: 77%
“…The assemblage comprises a low dwarfshrub canopy of Betula nana, Salix type B, and Andromeda polifolia, similar to the rim vegetation but containing a higher proportion of plants that have a greater water tolerance or occur commonly in raised bogs, such as Carex. In contrast to our study, Minke et al (2009) andDonner (2007) carried out comparable vegetation analyses in the northern Indigirka Lowland and identified Comarum palustre, Drepanocladus revolvens and Sphagnum squarrosum as common elements of vegetation in the rim-to-pond transition zone (in addition to Carex and Andromeda polifolia; de Klerk, 2008).…”
Section: Small-scale Spatial Structure Of Polygonscontrasting
confidence: 77%
“…This delay in immigration was probably not due to temperature limitations, as the Bølling period is known to have been favourable for the establishment of tree birch in the Danish region (Coope et al 1998;Renssen and Isarin 2001). It has been suggested that soil conditions and aridity could have prevented immigration until the middle of the Allerød (Mortensen et al 2011) and an increase in precipitation has been linked to the spread of tree birch and woodland development in northern Germany during this time period (Usinger 1998;De Klerk 2008;De Klerk et al 2001). Although it is problematic to use negative evidence to suggest the absence of tree birch from the Danish region until c. 13,600 cal.…”
Section: Resultsmentioning
confidence: 99%
“…During the early part of the Late Glacial (from 14.5 14 C ka BP) these areas could have been a mammoth refugium soon after deglaciation, because the vegetation remained open there during the early part of the Greenland Interstadial GrI-1e, probably because of a climatic gradient between the ice-free continental Central Europe and the decaying Scandinavian ice shield (de Klerk, 2008). On the other hand, in central Europe the pine/birch woodlands of Greenland Interstadial Gr-1 e-a (Bølling/Allerød) were largely replaced for nearly a thousand years by a subarctic open park tundra during Greenland Stadial 1 (Younger Dryas) in the northernmost parts of the European Lowlands (de Klerk, 2008). This open park tundra, only with scattered birch, was especially developed in the northernmost regions of what is now northeastern Germany.…”
Section: Palaeoecological Context and Colonisation Pattern Of The Latmentioning
confidence: 99%